PENDIDIKAN ISLAM DALAM PANDANGAN QADARIYAH, JABARIAH, DAN ASY’ARIYAH - St. Aisyah Abbas (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2016)
Education in the view Qadarites is the pattern of education that is free, it is reflected in the pattern of secular education, where the authority of learners is very high (free) to make his choice and the formation of his personality. This theory is akin to the theory of empiricism, behaviorism, where the child was instrumental education pen-and uncertain-right direction of human development. Education is the differences between humans and other humans. Further education in the view Jabariyah educational pattern is very weak from all aspects. This is reflected in traditional schools or pattern of early education. This theory is akin to navitisme theory in the philosophy of education, where education is considered unnecessary given to learners, because nature is decisive. While education in the view Asy'ariyah namely solidarity between educational pattern Qadarites with Jabariyah. Where the educational pattern Asy'ariyah criticizes secular as well as traditional models. The education pattern akin to the theory of convergence where the theory acknowledges the influence of faith in the form of a personal internal and external influences in the form of sociality in social activities. Pattern-ariyah Asy' education are highly relevant to the development of education today.